2021
DOI: 10.14710/mkts.v27i1.33861
|View full text |Cite
|
Sign up to set email alerts
|

A Note on The Design of Seawall for Tsunami Disaster Mitigation

Abstract: Many coastal structures or structures in coastal areas were destroyed by a tsunami attack. Such destructions were due primarily to the fact that such structures were not designed to withstand a tsunami. Those which were designed to withstand tsunami force may also have been destroyed due to some damaging factors which were not included in the design. The damage of the coastal structures is one of the important factors that have caused casualties. Especially, when the destroyed structures were originally aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Another research also mentioned that one of the materials that is able to protect the coast from tsunamis is sand dunes ( Figure 2 ). Triatmadja and Warniati ( 2021 ) stated that sand dunes are quite difficult to be breached by the tsunami. In the research to test the sand dunes in holding off the tsunami using physical and mathematical models by Triatmadja et al ( 2014 ), it was found that the lower the sand dunes from the tsunami, the more damage level of the sand dunes would be.…”
Section: Resultsmentioning
confidence: 99%
“…Another research also mentioned that one of the materials that is able to protect the coast from tsunamis is sand dunes ( Figure 2 ). Triatmadja and Warniati ( 2021 ) stated that sand dunes are quite difficult to be breached by the tsunami. In the research to test the sand dunes in holding off the tsunami using physical and mathematical models by Triatmadja et al ( 2014 ), it was found that the lower the sand dunes from the tsunami, the more damage level of the sand dunes would be.…”
Section: Resultsmentioning
confidence: 99%